Presenting Pattern and Treatment Modalities of Prostate Cancer in Nicrh - Karim, Howlader Fazlul; Islam, SK Amirul; Islam, Md Monowarul; Nag, Shuvendra Nath; Chowdhury, Mohammad Murad; Saha, Pranashis (Bangladesh Journal of Urology, 2020)
Objective: The aim was to describe the clinicopathological presentation of prostate cancer and the treatment modality in patients seen in Uro-oncology department of National Institute of Cancer Research & Hospital (NICRH), Bangladesh. Methods: Data were collected prospectively from all patients with diagnosed prostate cancer and managed in Uro-oncology department of NICRH from January 2016 to December 2017. Patient’s age, clinical presentation, prostate specific antigen(PSA) level, mode of diagnosis, Gleason sum score, stage of the disease at presentation and modality of treatment were recorded and analyzed. Results: There were 407 cases of histologically proven prostate cancer. Mean patient age was 69 years. About 87% presented as diagnosed prostate cancer. Twenty one(5%) patient presented with features of metastasis with unknown primary , we confirmed after prostate biopsy. About 77% of patients had a serum PSA above 20 ng/ml. Gleason sum score was 8 or more in 46% of patients. Metastases were found at the time of presentation in 85% of patients. Ten (2.5%) patients underwent radical radiotherapy, while two patients had radical prostatectomy. Most (68%) of the 347 patients who required androgen deprivation therapy had surgical orchiectomy. Conclusion: Bangladesh appear to be having a low incidence of prostate cancer, but a larger proportion of advanced and high grade cancers in comparison to the UK and USA. Although genetic differences may exist, a dietary or an environmental factor is more likely to be the cause for these changes. The protective effect of this factor appears to wane as South Asians emigrate and live in UK and USA. Bangladesh Journal of Urology, Vol. 21, No. 2, July 2018 p 56-61